Learning with Leaflet of Electronegativity (LoEN): Enhancing Students' Understanding on Electronegativity, Chemical Bonding, and Polarity - Erlina, E.; Cane, C.; Williams, D. P. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
Previous research has reported that many high-school and undergraduate students have difficulty explaining the relationship between polarity and electronegativity even though they may be familiar with the concept of polarity. This study aims to address these misconceptions using a leaflet and assess its effectiveness using questionnaires and concept testing.Ã‚Â A simple, colorful printable leaflet was produced and distributed to students in Indonesia. The Leaflet on Electronegativity (LoEN) provided students with an overview of the theoretical basis of the concepts and guidance on applying these principles. The leaflet format is cheap and easy to mass-produce, which is an important factor given the limited access to other types of appropriate learning resources in Indonesia. The leaflet formed the basis of a classroom discussion activity. Visualization is known to play an important role in constructing students' conceptual understanding, so the leaflet made extensive use of diagrams to explain relevant concepts. The leaflet was printed in full color to make it visually appealing and facilitate student learning. Students were tested before and after learning with the LoEN. A Paired-sample t-test using SPSS is used to compare the pretest and posttest scores to measure the effectivity of the LoEN.A statistically significant improvement in scores (p = 0.000) was achieved, which indicates that using the LoEN in the classroom helps students understand the topic. Also, students' positive responses signify that the LoEN provides an engaging way to learn the concepts.